2001
DOI: 10.1002/app.1727
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic disassociation of EVA random copolymer in dilute solutions

Abstract: Ultrasonic disassociation of the ethylene-vinyl acetate (EVA) random copolymer in 1,2-dichloroethane (DCE), cyclohexane (CYH), and their solvent mixtures was investigated using viscometry and dynamic laser light scattering (DLLS). It was found that the disassociation of the EVA aggregates in solutions increases with increasing the time and intensity of ultrasonic shearing and approaches invariant finally. This phenomenon is especially marked for the EVA copolymer with low vinyl acetate (VA) content in the pola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Theoretical and experimental results [3,6,7] report positive k H values that lie well within the range of 0 to C1 where the smaller numbers are reported for better solvents. Somewhat larger Huggins' constants of 0.7 or higher are found for polymers in solvents approaching the theta point.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Theoretical and experimental results [3,6,7] report positive k H values that lie well within the range of 0 to C1 where the smaller numbers are reported for better solvents. Somewhat larger Huggins' constants of 0.7 or higher are found for polymers in solvents approaching the theta point.…”
Section: Discussionmentioning
confidence: 70%
“…The well-known example is, of course, use of the intrinsic viscosity to measure average molecular weights via the Mark-Houwink-Kuhn-Sakurada (MHKS) relationship [2]. Among the many applications of dilute solution experiments on polymers appearing in the literature are those to determine average chain dimensions [3], aggregation [4], solvent power of mixed solvents [5], conformational transitions [6], the excluded volume and hydrodynamic effects (e.g. Fox and Flory) [7], polymersolvent interactions [8] and various types of polyelectrolyte behavior [9].…”
Section: Introductionmentioning
confidence: 99%
“…The values of [η] of samples as well as their polymerization conditions are listed in Table I. However, the other [η] of the PAAm at different external experimental conditions such as, added salt and pH of the solution were determined by the single point method with the equation,22 where the η r is the relative viscosity at a given solution concentration C . …”
Section: Methodsmentioning
confidence: 99%
“…Various techniques exist for the dispersion of particle agglomerates, such as the application of high shear forces during mechanical stirring and the direct incorporation by chemical methods . Another suitable alternative technique for the dispersion of nanoparticles is ultrasonication . For instance, Boukerrou et al successfully incorporated titanium dioxide nanoparticles into epoxy resin via the ultrasonic process.…”
Section: Introductionmentioning
confidence: 99%
“…Jun et al found that the dispersion and adhesion of B 4 C particles in epoxy resin can be enhanced by using direct ultrasonic excitation. Meanwhile numerous studies have shown that ultrasonication has an impact on the structure and crystalline order of a polymer . These studies have shown that ultrasonic treatment can degrade polymer chains.…”
Section: Introductionmentioning
confidence: 99%